Hypnoanalysis - Wolberg, Lewis R. (Lewis Robert), 1905-1988 (William Heinemann (Medical Books) Ltd., 1946)
Hypnoanalysis presents a critical review of a report on hypnoanalysis. The book discusses the advantages of this method; the the definite change in the functional organization of the patient; and the specific schizophrenic personality. Some of the topics covered in the text are the description of a hypnoanalysis case; the demonstration of the use of hypnosis in the treatment of a patient; and the developments in the application of the treatment. The narration of the patient's journal; the daily experiences of the patient as the treatment is continuing; and the dynamic interpretation of the exp.